Role and dynamics of 'Late-comers' in the global technology competition - Tran, Chung Anh (KIT Scientific Publishing, 2011)
Faster developing cycles and economic developments created many emerging economies in the 20th century. For sustainable economic growth, however, the construction and constant preservation of a profound knowledge base and technological pool is crucial. Brazil, China, India and Russia, experienced constant high economic growth rates and begun to evolve to solid economies which are challenging the established players. This book consists of a profound empirical analysis of these emerging economies.